Students' Opinions about Using MOODLE Platform for Learning Foreign Languages for Specific Purposes - Aleksandra Gojkov-Rajić; Јеlisaveta Šafranj (University of Belgrade, Teacher Education Faculty, 2019)
The paper presents the results of using the MOODLE platform for learning foreign languages for specific puproses. The aim of the paper is to examine the views of students who use this platform as an additional tool for learning. The method of systematic non-experimental observation was used in the research, and the data were collected using an assessment scale, i.e. a five-step Likerttype questionnaire and a scale with a binary response format, and tested with the SPSS statistical package. The starting question was - how students assess the importance of an LCMS (Learning Content Management System) tool for learning a foreign language for specific purposes. The sample is convenient and it consists of three hundred forty eight students of the Faculty of Teacher Education in Belgrade and the Faculty of Technical Sciences in Novi Sad. The variables are normative: general questions (department, gender, age, average grade during studies and the use of the ICT) and criteria-based statements: student attitudes, success in learning foreign languages. One of the most significant findings is that learning was improved by integrating the Moodle platform in foreign language learning. It promotes student-centered learning and supports the key values of the communicative approach to language learning, which students evaluate as the benefit of this tool. The data show that this approach instigates students to take teaching materials outside the classroom to practice their language skills. In addition, they downloaded and shared documents among themselves and with their teacher, and they were not limited by time and place.